Improving the Technical and Managerial Capacity of Catfish Farmers Through Smart Aquaculture in Malang Regency: Smart Farmers, Fat Wallets - Resi Dwi Jayanti Kartika Sari; Andrijani Sumarahinsih; Isman Isman; Khoirul Bahriyah; Muhammad Darul Fatoni; Muhammad Dicki Setiawan; Zuma Alif Zulfikar Sabbakha; Abdi Prawira Yudha (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Catfish farming plays a significant role in supporting rural economies in Indonesia, yet farmers still face challenges such as high seed mortality, limited financial record-keeping, and weak marketing strategies. These constraints reduce productivity and hinder the sustainability of hatchery businesses at the village level.Aims: This community service program aimed to strengthen the technical and managerial capacities of catfish farmers at the Mulyojoyo Sakti 1 People’s Hatchery Unit (UPR) in Maguan Village, Ngajum Subdistrict, Malang Regency, by integrating workshops, mentoring, and smart aquaculture practices.Methods: The program employed a quasi-experimental approach using a one-group pretest-posttest model. A total of 25 active farmers aged 30-50 years participated. Data were collected through questionnaires, observations, and practical tests to assess improvements in economic management and technical skills.Results: The findings revealed significant improvements in participants’ capacities. The average economic management score increased from 56.4 to 82.3, while technical skills rose from 59.1 to 85.6. The adoption of self-produced feed reduced operational costs by up to 15% and increased household net income by 12-20% per production cycle.Conclusion: The program effectively enhanced both technical and managerial skills of catfish farmers while promoting economic efficiency and business sustainability at the community level. This model demonstrates the importance of participatory approaches in empowering rural aquaculture enterprises.